RURAL OLDER ADULTS AND THE OPIOID CRISIS IN UTAH: THE CANARY IN THE COAL MINE - Edelman, L S (Innov Aging, 2018)
Rural America has been hard hit by the opioid epidemic with higher prescribing levels, more drug overdose deaths, and fewer treatment options than urban America. Prescription opioid misuse afflicts all ages. In rural areas of Utah, where the workforce is more likely to engage in blue-collar work such as mining, opioid use often begins after a work-related injury and continues into old age to combat the physical toll of years of physical labor. As a result, there are increasing concerns about rural older adult opioid misuse, increased risk of overdose or injury, and elder abuse. In particular, reports of older adults giving away or selling prescription opioids to supplement income are becoming more common. Increased research is needed to better understand rural older adult opioid prescribing patterns and misuse in order to educate health care providers about, and target community resources toward, this vulnerable group.